Propaedeutics to Any Future Philosophy in Indonesia - Harsawibawa Albertus (Ledalero Institute of Philosophy and Creative Technology (IFTK Ledalero), Indonesia, 2025)
The local wisdom of Indonesia has long been considered philosophy proper by a number of Indonesian thinkers; they proclaimed that “Indonesian philosophy”, or “filsafat Nusantara”, does exist. Based on a number of studies of Indonesian thoughts—some of them called themselves “philosophy”—that underwent the hardness test in the forms of comparative philosophy and ethnophilosophy/ethno philosophy/ethno-philosophy, what is referred to as Indonesian philosophy does not yet meet the requirements to be classified as such. The hardness test involved tracing a number of representative literatures and comparing the outcomes with the two tests. This article shows that ideas thought to be called philosophy actually fall under ethnophilosophy or ethno philosophy category. The study also illuminates a deficit in Indonesian’s philosophical thinking, which is the absence of either reception or refutation of preexisting ideas; there is no response to reveal the presence of dialectics—one of philosophy’s traits. Facing that situation, and thanks to the two hardness tests, this article offers the propaedeutics required for Indonesian thought to be in line with the great philosophies of the world.